Plant NLRs: Evolving with pathogen effectors and engineerable to improve resistance - Zhang, Biaoming; Liu, Mengting; Wang, Yanchao; Yuan, Wenya; Zhang, Haitao (Frontiers in Microbiology, 2022)
Pathogens are important threats for many plants throughout their lifetimes. Plants have developed different strategies to overcome them. In the plant immunity system, nucleotide-binding domain and leucine-rich repeat-containing proteins (NLRs) are the most common components. And recent studies have greatly expanded our understanding of how NLRs function in plants. In this review, we summarize the researches about the mechanism of NLRs in the processes of effector recognition, resistosome formation and defense activation. Typical NLRs are divided into three groups according to the different domains at their N termini and function in interrelated ways in immunity. Atypical NLRs contain additional integrated domains (IDs), some of which directly interact with pathogen effectors. Plant NLRs evolve with pathogen effectors and exhibit specific recognition. Meanwhile, some NLRs have been successfully engineered to confer resistance to new pathogens based on accumulated studies. In summary, some pioneering process has been obtained in NLR researches, though more questions arise as a result of the huge number of NLRs. However, with broadened understanding in mechanism, NLRs will be important components for engineering in plant resistance improvement.